FEATURES OF THE ANALYSIS AND AUDIT OF THE ECONOMIC ACTIVITIES OF ENTERPRISES UNDER THE CONDITIONS OF THE MARTIAL STATE - MYKHAILENKO, Olha; NIKOLAIENKO, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to study the peculiarities of the analysis and audit of the economic activity of enterprises in the conditions of martial law.Method. The research methodology, according to the author's version, is based on the following general and specific methods of scientific knowledge: the method of system analysis to determine the main changes that affected the processes of analysis and audit of economic activity; the method of content analysis to determine the impact of force majeure on the processes of analysis and audit of economic activity; the method of abstraction to determine the likely scenario of the development of events, provided that force majeure circumstances and the impact on the results of economic activity are avoided; methods of induction and deduction to determine the level of potential risk of occurrence of adverse events and rates of their development; methods of analysis and synthesis for building an algorithm for conducting analysis and auditing of the enterprise's economic activity.The results. Conducting the analysis of financial and economic activity is possible in several cases: 1) for the needs of the company's management, it is an operational, current and strategic analysis; and 2) when conducting an audit in order to identify the correctness and reliability of the display of accounting indicators in reporting documents. In the first case, the analysis involves adjusting the existing indicators for incurred losses and destroyed material and technical values, which are reflected in the balance sheet of the enterprise, and taking into account possible adverse events on economic activity in the short-, medium- and long-term periods of operation. The auditor, in turn, relies on the use of the existing audit methodology (international auditing standards), taking into account force majeure circumstances (including military actions and martial law) that caused losses and destruction of the company's property.Novelty. The process of analysis and audit of the company's financial and economic activity is systematized and modified, taking into account force majeure circumstances (including military operations and martial law).Practical value. The proposed methodology will be useful for teachers and students of higher education institutions teaching disciplines related to the audit and analysis of the economic activity of the enterprise, scientists and practitioners investigating the specified problems.
Keywords: martial law; analysis; audit; financial and economic condition; enterprise (organization)